Analisis laporan keuangan PT. Unilever Indonesia Tbk melalui pendekatan rasio solvabilitas dan profitabilitas: Studi kasus laporan tahun 2019-2023 - Khotimah, Husnul; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2024)
This study analyzes the financial statements of PT Unilever Indonesia Tbk using solvency and profitability ratios during the 2019-2023 period, including Gross Profit Margin, Return on Assets (ROA), Return on Equity (ROE), Debt to Asset Ratio (DAR), and Debt to Equity Ratio (DER). In the profitability ratio, although there is a decrease in several indicators, such as ROA which fell from 36.1% in 2019 to 27.5% in 2023, PT Unilever Indonesia still shows a good ability to manage its resources to generate profits. On the other hand, the solvency ratio shows a fluctuating trend. Debt to Asset Ratio (DAR) in 2023 decreased to 59%, indicating an increase in the contribution of own capital in funding the company’s assets. So that in overall general performance, the company’s financial health is in a fairly stable category, despite a decrease in several indicators. This demands more attention to ensure long-term business continuity and growth.